SEBARAN HORIZONTAL SUHU, SALINITAS DAN KEKERUHAN DI PANTAI DUMOGA, SULAWESI UTARA - M. Furqon Azis Ismail; Ankiq Taofiqurohman (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2012)
Horizontal Distribution of Temperature, Salinity and Turbidity in Dumoga Coastal Waters, North Sulawesi. Observation of water quality parameter namely temperature, salinity and turbidity were carried out in Dumoga Coastal waters on July 2006. The objective of this research is to know the horizontal distribution of temperature, salinity and turbidity which can be used to obtain the information regarding the feasibility of Dumoga Coastal waters for aquaculture. The methods were used are field observation using sensor system of CTD SBE 19. The result of the research shows that the water quality parameters in Dumoga Coastal waters there are no thermocline layer with water temperature between 24,22 °C – 28,53 °C. The presence of freshwater inputs from Dumoga River to the seaside with salinity varies from 4,66 psu – 33,89 psu. The turbidity are relatively high with values between 8,33 NTU – 272,59 NTU. Viewed from temperature, salinity and turbidity, the Dumoga Coastal waters still within the tolerance limits for tropical aquaculture. Keywords: temperature, salinity, turbidity, Dumoga Coastal waters